Evaluation of Lithium Monitoring Practices for Patients in a Community Mental Health Team: An Audit Report. - Abdulrahman Nafiu; Usman Siddique; Deepak Moyal (BJPsych Open)
Aims: This audit aimed to assess the adherence of lithium monitoring practices within the Enhanced Teams of Folly Hall Community Mental Health Team (CMHT) to national and local guidelines. By identifying gaps and areas for improvement, the audit sought to enhance patient safety, optimize lithium therapy outcomes, and support service improvements.